2013
DOI: 10.1016/j.pain.2013.03.032
|View full text |Cite
|
Sign up to set email alerts
|

Natural course of acute neck and low back pain in the general population: The HUNT study

Abstract: In this prospective cohort study we aimed to describe the natural course of acute neck and low back pain in a general population of Norway. We screened 9056 subjects aged 20-67 years who participated in a general health survey for a new episode of neck or low back pain the previous month. The screening identified 219 subjects who formed the cohort for this study. Pain intensity was reported on a numeric rating scale (0-10) at 1, 2, 3, 6, and 12 months after start of the new pain episode. The course of pain was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
92
1
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(111 citation statements)
references
References 35 publications
7
92
1
11
Order By: Relevance
“…In contrast, passive treatments might not be the best way to obtain necessary behavioral changes that require active and motor control exercises. 45,46 Thus, our experimental and comparator treatments may not have been in complete equipoise.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, passive treatments might not be the best way to obtain necessary behavioral changes that require active and motor control exercises. 45,46 Thus, our experimental and comparator treatments may not have been in complete equipoise.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 For acute pain, treatment appears to have little effect on persistence. 23 Factors that may be associated with poorer prognosis include female sex, older age, coexisting psychosocial pathology, and radicular symptoms ( Table 1).…”
Section: Natural Course Of Neck Painmentioning
confidence: 99%
“…23 Factors that may be associated with poorer prognosis include female sex, older age, coexisting psychosocial pathology, and radicular symptoms ( Table 1). [22][23][24][25][26] A study by Gore et al 27 performed in patients with long-standing or recurrent neck pain found that individuals with more severe pain following an injury and those with symptoms or signs of cervical radiculopathy had a greater likelihood of persistent pain, although a formal statistical analysis was not performed for evaluation of radiculopathy. No association was found between the degree of radiographic degeneration and satisfaction with treatment results.…”
Section: Natural Course Of Neck Painmentioning
confidence: 99%
“…The results from adult population studies oppose the findings within this current review, which suggest no or little risk for children and adolescents. Examination of the literature on adults does shows that most reported evidence of risk are for chronic musculoskeletal outcomes or for widespread pain, which is suggestive of a higher level of pain severity or severity threshold (ie, chronic pain samples and those with widespread pain often report higher levels of pain severity 45 ), and second outcomes such as chronic pain may include populations where pain was present before the measurement of outcome and therefore potentially enable a reciprocal relationship between sleep and pain. 46,47 Taking a wider epidemiological view, there is estimations of 75-80% lifetime prevalence of musculoskeletal pain in adult populations, 48 and therefore it may be difficult to assert within those populations that this would be their first ever experience of musculoskeletal pain, as they may have experienced musculoskeletal pain before.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%